1979
DOI: 10.1051/parasite/1979541001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium chabaudi : Modification des acides sialiques de surface des hématies au cours de l’infestation

Abstract: Résumé.Les acides sialiques de surface des hématies de souris infestées par le parasite Plasmodium chabaudi sont augmentés comparativement à ceux d'hématies de souris non infestées. Cette augmentation coïncide avec celle des réticulocytes circulants. Une augmen tation similaire des acides sialiques de surface est montrée par l'étude des réticulocytes induits par phénylhydrazine. De la même façon, les oses neutres et le fucose sont trouvés en quantité plus importante dans les glycopeptides trypsiques de surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Uninfected cells from heavily infected mice have less sialic acid than normal mouse RBC. Finally, studies in Swiss mice with the self-curing malaria P. chabaudi showed that the sialic acid content of parasitized RBC increased over that of normal RBC in direct proportion to the degree of reticulocytosis (Fabia et al 1979). Our results for P. berghei SI-RBC were similar to the extent that these cells also had a high sialic acid content like reticulocytes.…”
Section: Discussionsupporting
confidence: 72%
“…Uninfected cells from heavily infected mice have less sialic acid than normal mouse RBC. Finally, studies in Swiss mice with the self-curing malaria P. chabaudi showed that the sialic acid content of parasitized RBC increased over that of normal RBC in direct proportion to the degree of reticulocytosis (Fabia et al 1979). Our results for P. berghei SI-RBC were similar to the extent that these cells also had a high sialic acid content like reticulocytes.…”
Section: Discussionsupporting
confidence: 72%